Fructan content in most commonly consumed Slovenian foods and estimation of daily fructan consumption - Ferjančič, Blaž; Korošec, Mojca; Kočevar Baloh, Ana; Bertoncelj, Jasna (Frontiers in Nutrition, 2024)
Fructans can be considered as part of the group of fermentable oligo-, di-and monosaccharides and polyols (FODMAPs). Short-chain fructans have a rapid fermentation rate and can thus, worsen symptoms in patients with irritable bowel syndrome. In this study, the fructan content in 40 of the most commonly consumed foods in Slovenia was measured. Overall, the fructan content was relatively low: 0.1-1.97 g/100 g fresh weight. The highest fructan content was found in onion (1.97 g/100 g), followed by wheat flour (0.75 g/100 g). A simple model for calculating fructan intake was developed based on the results of the SI.Menu 2017/2018 national survey, which collected data on the frequency of intake of different foods and food groups (expressed in g/day). After calculating the daily intake of the surveyed foods, we used our results on fructan content to estimate daily fructan consumption. Mean daily fructan intake reaches 1.6-1.7 g/day, with no differences between men and women. Our assessment of fructan intake at the national level represents the first step towards the creation of a database on FODMAP intake.